The impacts of international ship and port facility security (ISPS) code on port users at port of Tanjung Pelepas - Rafikah, Mohd Daud (2014)
International ports and sea transportation celebrating the tenth years of implementation of International Ship and Port Facility Security Code (ISPS) Code under International Convention for the Safety of Life at Sea (SOLAS) 1974. Therefore, this study aimed at identifying the impacts of ISPS Code implementation on port users at Port of Tanjung Pelepas (PTP). The method used in this study was qualitative using interview as the means for data collection. The interviews were done with respondents based on three categories of port users namely freight forwarder, shipper and logistic company. Through the qualitative data analysis, it showed that the impacts of ISPS Code implementation at PTP have direct impacts such as cost increased and changes in procedure on port user organization and activities as any port user is compulsory to comply with port regulations to ensure port security. This study found that the code implementation is not significantly affecting the port user performance. This study suggests that there is a need to further the study of ISPS Code in port in the future by taking into account more different perspectives of the diversity of the parties involved in port operations.